2021
DOI: 10.3390/v13091772
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Milk Tank Samples Are Suitable to Assess Circulation of Tick-Borne Encephalitis Virus in High Endemic Areas

Abstract: A reliable surveillance strategy of tick-borne encephalitis virus (TBEV) is necessary to ensure adequate disease control measures. However, current approaches assessing geographical TBEV circulation are ineffective or have significant limitations. In this study we investigated a total of 1363 goat and 312 sheep bulk tank milk samples for the presence of TBEV. Samples were collected from systematically selected farms in Lithuania every 4–5 days from April to November in 2018 and 2019. To validate results, we ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…According to various studies, the reported minimal infection rate (MIR) in ticks ranged from 0.1 to 1.8% [20,32,33]. Nevertheless, recent studies confirmed widespread TBEV distribution in the country based on the prevalence rate of antibodies against TBEV in horses (37.5%) and virus presence in horse serum samples (3.9%), as well as in goat (4.3%) and sheep (4.5%) milk samples collected in endemic localities in Lithuania [34,35]. Moreover, in a recent study, TBEV-specific antibodies were detected in 21.6% and TBEV RNA in 18.6% of randomly collected blood serum samples of dogs residing in the secondlargest city in Lithuania.…”
Section: Discussionmentioning
confidence: 99%
“…According to various studies, the reported minimal infection rate (MIR) in ticks ranged from 0.1 to 1.8% [20,32,33]. Nevertheless, recent studies confirmed widespread TBEV distribution in the country based on the prevalence rate of antibodies against TBEV in horses (37.5%) and virus presence in horse serum samples (3.9%), as well as in goat (4.3%) and sheep (4.5%) milk samples collected in endemic localities in Lithuania [34,35]. Moreover, in a recent study, TBEV-specific antibodies were detected in 21.6% and TBEV RNA in 18.6% of randomly collected blood serum samples of dogs residing in the secondlargest city in Lithuania.…”
Section: Discussionmentioning
confidence: 99%
“…Research conducted at the Institute of Rural Health in Lublin confirmed the presence of TBE virus in sheep’s milk at 22%, in goat’s milk at 20%, and in cow’s milk at 11%; however, it should be noted that the milk samples came mainly from animals grazing on pastures, where the risk of tick bites is higher than in farm breeding [ 22 ]. Despite this, most milk sample testing focuses on specific food outbreaks rather than epidemiological screening; therefore, the percentage of positive results will vary in different countries [ 23 ]. In Lithuania, the percentage of positive results of bulk-tank milk from sheep and goats has been confirmed at the level of 4.3% and 4.5%, respectively [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, most milk sample testing focuses on specific food outbreaks rather than epidemiological screening; therefore, the percentage of positive results will vary in different countries [ 23 ]. In Lithuania, the percentage of positive results of bulk-tank milk from sheep and goats has been confirmed at the level of 4.3% and 4.5%, respectively [ 23 ].…”
Section: Discussionmentioning
confidence: 99%